Design and implementation of electromagnetic soft surfaces for decoupling in between two microstrip patch antennas. Issue 10 (3rd July 2018) - Chen, Hai-Yan; Li, Min-qing; Deng, You-Jie; Weng, Xiao-long; Xie, Jian-Liang; Deng, Long-Jiang
Abstract: In this paper, the design of the electromagnetic soft surfaces realized by metal strips loaded with C-shaped slots is demonstrated having good suppression of electromagnetic coupling in between two patch antennas. Electromagnetic bandgap properties of the as-prepared electromagnetic soft surfaces with C-shaped slots loading is proposed for normal incidence, and compared with that from the one of the same size but none C-shaped slots on the patches. The proposed structure possesses excellent miniaturization properties with working frequency of bandgap toward lower frequency but keeping the filtering level unchangeable. Then, the proposed structure is loaded in two patch antennas for decoupling in between them. Experimental results are presented and compared to numerical simulations, and they demonstrated that the proposed electromagnetic soft surfaces loading advances excellent suppression of electromagnetic coupling and the coupling decrease about 17 dB near the working frequency band.